GAMBARAN HISTOLOGIK RAMBUT PANJANG ANJING UMUR MUDA DAN UMUR TUA - , LATIFA RIZQY ARIFINIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hair is part of the dog's body that covers almost the entire body except for some specific areas such as the nose and feet. Hair can be divided into two part, root and shaft. Hair shaft consists of three layers: the cuticle, the cortex and medulla. This research was conducted with the aim to distinguish long hair on young dogs and old dogs based on the thickness of the cuticle, cortex and medulla. Eight samples of long hair dogs were used in this research, consisted of four samples were youngers and four samples were olders. The method were used in this research by making histology of hair by hematoxylin-eosin (HE) staining, and measuring the thickness of the cuticle, cortex and medulla. Each structure was measured at three different points and then calculated the average for each sample. The results of the study would be analyzed using T-test. The results of the study showed that young dogs had cuticle, cortex and medulla which were thicker than in old dog. However, the results which were analyzed by statistical using T-test showed that there was no significant difference (P>0.05) between long hair on young dogs and old dogs. Keywords: long hair, aging, histological structure